Book review of Bogusławska-Tafelska, M. 2016. Ecolinguistics: communication processes at the seam of life. New York: Peter Lang - Zhou, Wenjuan (Scripta Neophilologica Posnaniensia, 2019)
Book review of Bogusławska-Tafelska, M. 2016. Ecolinguistics: communication processes at the seam of life. New York: Peter Lang